New trends of additive manufacturing using materials based-on natural fibers and minerals : A systematic review - Joao Ribeiro; Manuel Rodríguez-Martín; Joaquín Barreiro; Ana Fernández-Abia; Roberto García-Martín; Joao Rocha; Susana Martínez-Pellitero (Heliyon)
Polymeric materials based on natural fibers and minerals are currently being researched and their development is still in its infancy but is expected to increase in the coming years (being nowadays a hot topic). Their main advantage is that they make it possible to use waste and by-products of agricultural, forestry, and mineral origin to generate materials for Additive Manufacturing. Since their use reduces the need for other synthetic polymers derived from petroleum and other non-natural fibers that generate a high environmental impact, this type of material is a sustainable, environmentally friendly, biodegradable solution that can be integrated into the value chain of certain industries and, finally, favors the circular economy. This study presents a bibliometric analysis, meta-analysis, and systematic literature review focusing on plant-based fibers and minerals in biocomposites from a holistic perspective. To learn about the potential of these new materials at an industrial level and to learn about the benefits they can have for society, the strengths, weaknesses, opportunities, and threats have been evaluated. The results strongly suggest that these materials will undergo intensive development in the upcoming years, with a substantial increase in their integration across industries.